Meningkatkan Kemampuan Siswa Memahami Gerak Benda Melalui Penerapan Metode Make A Match Pada Mata Pelajaran Ilmu Pengetahuan Alam Kelas 3 Madrasah Ibtidaiyah An-Nisaa Kota Batam - Rini Nofrita (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
his research is motivated by the problems of low ability students in the learning of Natural Sciences at the Government Elementary School An-Nisaa Batam. The ability of the students brought Minimum Criteria for completeness (KKM) that has been determined, this happens because the learning is dominated by lecture method so as to make the students feel bored. Therefore, teachers strive to implement methods make a match in order to create an atmosphere of learning interesting and fun. Purpose of this research would like to improve student learning outcomes by applying methods make a match on the subjects of natural science class 3 Government Elementary School An-Nisaa Batam. This study uses Advanced Research Methods Class Action model Make a Match studies conducted in two cycles, one cycle is executed only once the action research. Subjects were 3 classes of 30 people consisting of 14 men and 16 women, held in the second semester of 2014-2015 academic year between the months of March 2014 to April 2015 with the observation sheet and test sheet for action and documentation of the learning activities. Based on the results of the study show that learning methods make a match proven to improve student learning outcomes Islamic Elementary School Grade 3 An-Nisaa Batam on the motion of material objects. This can be shown by the increase in the percentage of mastery learning students with the results of the percentage of 40%; 60% and 90% in cycle 1 and cycle 2. Thus we can conclude that the method of learning make a match can improve learning outcomes of science students in grade 3 Government Elementary School An-Nisaa.